'Walking a tight rope': an investigation of nurse managers' work stressors and coping experiences. (February 2013) - Udod, Sonia A.; Care, W. Dean
Competing demands and a nursing shortage have contributed to a managerial workforce that is overworked and a health care environment that is under constant tension. The short supply and high turnover of manager positions, upwards of 30% in some regions in Canada, have contributed to an unstable work environment. The aim of this study examined the stress experiences and coping strategies of nurse managers in an acute care setting. Semi-structured interviews of five nurse managers were included in this pilot study. Qualitative content analysis was used to analyse the transcribed text. Six descriptive themes related to work stressors were identified: fiscal responsibilities, inadequate human resources, managing others, intrapersonal distress, middle management role and competing priorities. Three descriptive themes related to coping strategies were identified: peer and superior support, cognitive coping strategies and social and personal strategies. Findings indicate that coping mechanisms lessened the work stressors experienced by managers, but it was not always evident managers felt confident in their ability to cope effectively. Senior nurse leaders play an integral role in assuming responsibility for equipping managers with appropriate preparation and support to facilitate their success and to enhance the attractiveness of the manager role to potential recruits.